Elongator mutation in mice induces neurodegeneration and ataxia-like behavior - Marija Kojic (Nature Portfolio, 2018)
Elp6 is a component of the Elongator complex that regulates tRNAs and translation. Here the authors identify a mutation in the Elp6 gene that contributes to the cerebellar ataxia-like phenotype in a mutant mouse.